Paradigma Pembelajaran Pendidikan Agama Islam Berwawasan Integratif - Musmuallim Musmuallim (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This paper describes the vision of integrative learning paradigm PAI as an effort towards the development of a new scientific paradigm that integral (comprehensive). PAI-minded new paradigm of integrative learning is thinking and perspective constantly need to be developed through practice to integrate education between religion and science. At this paradigm, learning PAI wants to develop there are three things you want to develop. The first, which eliminates the educational process or there is no dichotomy between science and religion, and science is not value-free but free assessed. In addition, the teaching of religion with science and language not only teaches the traditional side, but also the rational side. Second, building science and advancement of integrative life between the spiritual, moral and material for human life. hird, humans are able to build competition and prepare a better life in the form of humans democratic, competitive, innovative based on Islamic values . Keywords: paradigm, PAI, integrative.